Real and Distributive Effects of Petroleum Price Liberalization : The Case of Indonesia - Clements, Benedict (IMF Working Papers; Working Paper ;, 2003)
The impact of higher petroleum prices on the aggregate price level, real growth, and income distribution is appraised within a multisector computable general equilibrium (CGE) model. A reduction in the government subsidy raises petroleum prices and production costs throughout the economy. Consumer demand, production, and income decline as output prices increase and consumer purchasing power decreases. The model is applied to and calibrated for Indonesia. The simulated results predict a slight increase in price level and a slight decrease in output. An important result is that urban household groups will be the most significantly affected by the subsidy reduction.